Associations of COVID-19-Related Health, Healthcare and Economic Factors With Prenatal Depression and Anxiety - Lyndsay A. Avalos (International Journal of Public Health, 2022)
Objective: This study evaluated whether COVID-19 pandemic-related health, healthcare and economic factors during pregnancy are associated with prenatal depression and anxiety.Methods: We conducted a cross-sectional study of 6,628 pregnant members of Kaiser Permanente Northern California who responded to a survey between 22 June and 30 September 2020. The survey included questions about depression (Patient Health Questionnaire) and anxiety (Generalized Anxiety Disorder) symptoms and COVID-19-related health and healthcare (e.g., had COVID-19) and economic (e.g., food insecurity) factors.Results: Over one third of individuals reported depression (25% mild, 8% moderate, 3% severe) or anxiety (22% mild, 8% moderate, 5% severe) symptoms. In multivariable analyses, COVID-19 during pregnancy, employment with greater risk of COVID-19, distress over changes in prenatal care, job loss, changes in childcare and food insecurity were associated with greater odds of prenatal depression or anxiety.Conclusion: Findings suggest the COVID-19 pandemic may have severe mental health repercussions for pregnant individuals. Support services for pregnant individuals experiencing these COVID-19-related factors and monitoring of those who had moderate/severe prenatal depression and anxiety symptoms during the COVID-19 pandemic is warranted.